A critical analysis of the process of intervention of the Ruiz Dávila hospice - Garro Aponte, Rolando (2019)
The process of intervention of the Ruiz Dávila Hospice, a nineteenth-century building located in the Historic Center of Lima, was carried out between 2010 and 2012. Furthermore, the finished works were inaugurated in June of this last year. In the development of the works, there were a series of stages such as the conditioning of the environments, the dismantling of some structures, the construction works, the complementary works, the follow-up, the documentation of the work and finally its inauguration. All this was done not by the work of a single person, but by a group of professionals with diverse skills and extensive experience, whose joint work can be seen today. The final product has had, however, both its critics and its defenders. In the first group, there are mostly university students and some authorities of the culture sector, the reason of their discrepancy being the new use and the introduction of modern materials. In the opposite wing, there is the community of architects, whose approval was clearly manifested with the official delivery of some prizes to those who were in charge of the intervention.